“That’s the Way to Wooooo it!”: Punch and Judy in Jamesian Ghost Stories: Punch and Judy in Jamesian Ghost Stories - Hill, Trevor (Acta Neophilologica, 2022)
M.R. James is known as a master of the ghost story, giving his name to a sub-genre. This article explores his use of the traditional Punch and Judy puppet show in his short story The Story of a Disappearance and an Appearance and the subsequent use by two modern authors, Christopher Harman and D.P. Watt, writing in the Jamesian style. The article considers the association between puppets and the occult before examining aspects of the show and how representations of historic and contemporary performances differ. Finally, the authors’ utilization of the Punch and Judy tradition in the stories is analyzed.